Dimensions of the Argentine Crisis 2001/02. A Critical Survey of Politico-Economical Explanations - Thomas Bernhardt (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: When the Argentine economy collapsed in the final days of December 2001, in fact, this did not come too much as a surprise. The country had entered its fourth consecutive year of recession and scepticism about the sustainability of its economic model was widespread. However, the magnitude of the collapse was both surprising and terrifying. In 2002, Argentina's real GDP slumped by approximately eleven percent, gross fixed investment fell by 36.4 percent and private consumption by 14.4 percent. After almost an entire decade of price stability, in 2002, the inflation rate shot up to an annual 41 percent and capital flight added up to more than twelve billion U.S. dollar. This economic misery was accompanied by social unrest and political turmoil. Living standards of the majority of Argentineans had deteriorated considerably in the second half of the 1990s. In mid-2002, open unemployment stood at 21.5 percent and poverty had risen dramatically, aff ecting 52 percent of urban population.
Keywords: 330